2015
DOI: 10.1080/10942912.2015.1020390
|View full text |Cite
|
Sign up to set email alerts
|

Fat Mimicking Properties of Citric Acid Treated Sweet Potato Starch

Abstract: Fat mimicking properties of citric acid treated sweet potato starch were investigated in this present study. Citric acid treated sweet potato starch was prepared by treating the native sweet potato starch with 3% citric acid for 6 h at a temperature of 45°C. Dextrose equivalent value of citric acid treated sweet potato starch was 2.05%. A significant increase in amylose content was noticed in citric acid treated sweet potato starch possibly due to the lyses of amylopectin fractions. The melting temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Starch granules were found to conglutinate in CTS2 and CTS4 which was due to the acid erosion on the core part of the granules. Similar result was noticed in the study conducted by Babu et al [65]. The extent of visible degradation was increased when the granules were subjected to a higher hydrolysis time and acid concentration.…”
Section: Scanning Electron Micrograph (Sem)supporting
confidence: 85%
“…Starch granules were found to conglutinate in CTS2 and CTS4 which was due to the acid erosion on the core part of the granules. Similar result was noticed in the study conducted by Babu et al [65]. The extent of visible degradation was increased when the granules were subjected to a higher hydrolysis time and acid concentration.…”
Section: Scanning Electron Micrograph (Sem)supporting
confidence: 85%
“…Regarding thermal parameters of the starches (Table 3), acidification reduced the onset temperature (To) for CS. Reduction in To by acid treatment has been previously reported for sweet potato and corn starches (Wang et al, 2003;Surendra Babu et al, 2016). However, the addition of proteins reversed this effect (Table 3).…”
Section: Characterisation Of the Protein-enriched Starchessupporting
confidence: 60%
“…This is in conformity to the earlier studies by Tulyathan et al [12] In previous studies, oval and round shapes have been reported for potato starches and native beans, [24] while oval and spherical shapes were reported for the field pea. [11] Roughness on the surface of acid-thinned ( Fig. 4) and acetylated ( Fig.…”
Section: Morphological Propertiesmentioning
confidence: 99%
“…[10] Another most important use of modified starches with respect to the health is as fat replacer, which gives more benefits to product developers and at last consumer can use a reduced fat food. [11] The aim of this work was to characterize selected properties of the native starch isolated from water chestnuts by means of chemical composition, scanning electron microscopy (SEM), swelling properties, solubility, and pasting properties. The present study will contribute to improved knowledge of physicochemical properties of water chestnut starch and explore its effective utilization in food products.…”
Section: Introductionmentioning
confidence: 99%